Middle East and North Africa Economic Monitor, April 2018 : Economic Transformation - Arezki, Rabah; Mottaghi, Lili; Barone, Andrea; Fan, Rachel Yuting; Kiendrebeogo, Youssouf; Lederman, Daniel (Washington, DC: World Bank, 2018)
After a sharp fall in 2017, economic growth in MENA is projected to rebound to 3.1 percent in 2018, thanks to the positive global outlook, oil prices stabilizing at relatively higher levels, stabilization policies and reforms, and recovery and reconstruction as conflicts recede. The outlook for MENA remains positive, and the growth rebound is expected to gain momentum over the next two years, exceeding 3 percent in 2020. While stabilization policies have helped economies adjust in recent years, .a second phase of reforms is needed should be transformative if the region is to reach its potential and create jobs for hundred million young people who will enter the labor market in coming decades. In this report, we explore the role that public-private partnerships can play. not only in providing an alternative source of financing but in helping change the role of the state from the main provider of employment to an enabler of private sector activity. Studies have shown that the gap between MENA economies and fast-growing ones is the performance of the services sector. The disruptive technology offers new opportunities for boosting private-sector-led growth through enhancement of high-tech jobs in the services sector. The report argues that combining the region's fast-growing pool of university graduates and a heavy penetration of social media and smartphone, could serve as the foundation for a digital sector that could create much-needed private sector jobs for the youth over the next decade.